Host-microbiota interactions in mammals - Hanski, E (2022)
The mammalian gut microbiota provides important functions for the host but at the same time varies greatly between species, populations, individuals and even within individuals over time. Drivers of this variation and particularly their relative importance remains poorly understood. Further, a large proportion of gut microbiota research has been conducted using the laboratory mouse as a model organism. However, laboratory mice inhabit an artificial world where individuals are inbred, the environment is stable, and microbial exposures are limited. As a result of domestication, the gut microbiota of laboratory mice differs in notable ways from that of their wild relatives, and studies investigating the gut microbiota of wild house mice have great potential to aid the interpretation of findings from the laboratory. In this thesis, I explore how the gut microbiota varies between laboratory and wild mice, and examine drivers of natural gut microbiota variation among and within wild mouse populations. I show that although wild mice have a compositionally and functionally more diverse gut microbiota with a faster turnover rate that is clearly shaped by their more complex environment, major patterns of gut microbiota assembly during early life are conserved between laboratory and wild house mice. Since the gut microbiota showed strong age-related variation, I developed a non-invasive epigenetic clock-based method for assessing age in wild mice, whose application showed promise for future studies estimating biological (if not chronological) age in this system. Gut microbiota composition was also influenced by spatial factors, with stronger effects on the fungal than bacterial components of the microbiota, and microbial transmission from soil was identified as one possible source of spatial variation. Finally, I investigate gut microbial ecology in a mammalian species that is quite the opposite of a model organism, the critically endangered Saiga antelope which suffers periodic mass mortality events. I characterise healthy gut microbiota in comparison to other similar species, providing important background for future conservation efforts, as well as contributing to our broader understanding of what shapes microbiota among mammals. Together the results from this thesis increase our understanding of the gut microbiota variation but also highlight challenges in studying the gut microbiota, in the laboratory and beyond.